Lab-on-a-CD: A Fully Integrated Molecular Diagnostic System. (June 2016) - Kong, Ling X.; Perebikovsky, Alexandra; Moebius, Jacob; Kulinsky, Lawrence; Madou, Marc
The field of centrifugal microfluidics has experienced tremendous growth during the past 15 years, especially in applications such as lab-on-a-disc (LoD) diagnostics. The strength of LoD systems lies in its potential for development into fully integrated sample-to-answer analysis systems. This review highlights the technologies necessary to develop the next generation of these systems. In addition to outlining valving and other fluid-handling operations, we discuss the recent advances and future outlook in four categories of LoD processes: reagent storage, sample preparation, nucleic acid amplification, and analyte detection strategies.